Pendampingan Pembelajaran Ilmu Tajwid untuk Meningkatkan Kemampuan Membaca Al-Qur’an di Desa Wangen Kecamatan Glagah Lamongan - Nisa', Khoirun; Nashihin; Tifrizzi, Muhammad (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Most of the children of Wangen village can read the Koran without spelling, but they pay little attention to the recitation, starting from the length and shortness, the nature of the letters, and the makhorijul of the letters as well as the lack of attention from the ustadzah, parents, and also from the surrounding community. And in TPA, those who have studied the science of Tajwid but have not been able to apply it to the literature they read, plus there are still small children who are not yet able to differentiate one letter from another so they need special attention. This assistance method uses the PAR (Participatory Action Research) method, namely research by identifying a problem in the field, then inserting an action as an answer or solution to the problem that has been identified. The initial activity is Identification with in-depth interviews with the head of the RW and the TPA teacher. Then it continues with the Problem Solving stage by collecting data and information from the students from the Koran teacher, and the final stage is Action As Solution, namely creating a Koran reading activity. fashahah by using correct tajwid and assistance in the form of coaching and training guidance to the students. As a result of this dedication, children can read the Koran fluently and use tajwid correctly. This activity is divided into three classics, namely; Opening activities (early Classical), core activities and closing activities (late Classical). Having a place to study the Koran at the RW Chairman's house every evening is a means for gathering and interacting with each other, because having this learning facility can increase children's knowledge, especially in terms of correct and appropriate reading of the Al-Qur'an.